Table of contents and introductory materials for Vol. 23, no. 6, Spring-Summer 2018 - Bruce Quantic (The Advocate, 2018)
Table of contents, editorial information, a message from the president of ATE-K, and a message from the editor for Vol. 23, no. 6, Spring-Summer 2018 for The Advocate.